2017
DOI: 10.1002/navi.213
|View full text |Cite
|
Sign up to set email alerts
|

Real-Time Ionosphere Monitoring by Three-Dimensional Tomography over Japan

Abstract: This paper reports on the development of a real-time three-dimensional ionospheric tomography technique using GNSS measurements. GPS measurement data from 200 GPS receivers distributed throughout Japan are analyzed in real time to calculate ionospheric Total Electron Contents (TECs). The three-dimensional ionospheric electron density distribution was reconstructed using the tomography technique from the slant TEC data. The tomography results were found to be in good agreement with both the electron density pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
42
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 32 publications
(47 citation statements)
references
References 13 publications
(19 reference statements)
3
42
0
Order By: Relevance
“…Yin et al (2006) studied the hmF 2 variations during three geomagnetic storms using the Multi‐instrument Data Analysis System (MIDAS) (Mitchell et al, 2002), and their results showed a dramatic increase of hmF 2 during geomagnetic storms. The constrained least squares method (Seemala et al, 2014) is used to reconstruct the density perturbations during medium‐scale traveling ionospheric disturbance (MSTID) events (Chen et al, 2016) and to develop real‐time three‐dimensional ionosphere monitoring (Saito et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Yin et al (2006) studied the hmF 2 variations during three geomagnetic storms using the Multi‐instrument Data Analysis System (MIDAS) (Mitchell et al, 2002), and their results showed a dramatic increase of hmF 2 during geomagnetic storms. The constrained least squares method (Seemala et al, 2014) is used to reconstruct the density perturbations during medium‐scale traveling ionospheric disturbance (MSTID) events (Chen et al, 2016) and to develop real‐time three‐dimensional ionosphere monitoring (Saito et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…To improve on estimations of climatologic models and still obtain a full 3‐D picture of the ionosphere, tomography techniques have extensively been applied (e.g., Hong et al, ; Raymund et al, ; Saito et al, ; Seemala et al, ; Ssessanga et al, , ; Tsai et al, ). However, ionosphere tomography techniques have a deficiency of not being able to adequately spread observation information within the grid, specifically over remote areas where measurements are lacking.…”
Section: Introductionmentioning
confidence: 99%
“…Computerized ionospheric tomography is an effective way to study 3D structures of ionospheric electron density (Austen et al 1988), particularly in a region with densely deployed GNSS stations (Seemala et al 2014;Chen et al 2016;Saito et al 2016). Here, we study the 3D structure of Es irregularities by performing 3D tomography of electron density anomalies using the GNSS-TEC data.…”
Section: Introductionmentioning
confidence: 99%